Deciphering the potential role of post-translational modifications of histones in gastrointestinal cancers: a proteomics-based review with therapeutic challenges and opportunities - Farrokhi Yekta, Reyhaneh; Farahani, Masoumeh; Koushki, Mehdi; Amiri-Dashatan, Nasrin (Frontiers in Oncology, 2024)
Oncogenesis is a complex and multi-step process, controlled by several factors including epigenetic modifications. It is considered that histone modifications are critical components in the regulation of gene expression, protein functions, and molecular interactions. Dysregulated post-translationally modified histones and the related enzymatic systems are key players in the control of cell proliferation and differentiation, which are associated with the onset and progression of cancers. The most of traditional investigations on cancer have focused on mutations of oncogenes and tumor suppressor genes. However, increasing evidence indicates that epigenetics, especially histone post-translational modifications (PTMs) play important roles in various cancer types. Mass spectrometry-based proteomic approaches have demonstrated tremendous potential in PTMs profiling and quantitation in different biological systems. In this paper, we have made a proteomics-based review on the role of histone modifications involved in gastrointestinal cancers (GCs) tumorigenesis processes. These alterations function not only as diagnostic or prognostic biomarkers for GCs, but a deeper comprehension of the epigenetic regulation of GCs could facilitate the treatment of this prevalent malignancy through the creation of more effective targeted therapies.